The Battle Of Bubble And Squeak - "Pearce, Phillipa" (Puffin Books: London, 2000)
A family battle erupts when Sid's gerbils, Bubble and Squeak are discovered. Sid's mum is determined to get rid of them, but this proves more difficult than expected.
Keywords: Juvenile works